Strategi Manajemen Pendidikan Islam dalam Meningkatkan Mutu Pendidikan di MTs Negeri 1 Pandeglang - Nana Suryapermana; Moch. Subekhan; Mamat Rahmatullah; Paiman Paiman; M. Luthfi (Universitas Islam Negeri Sumatera Utara Medan, 2026)
Amid the growing demands of educational modernization, madrasas are expected to balance academic excellence with the internalization of spiritual values. However, this effort is often hindered by partial and context-sensitive management approaches. Existing studies also tend to overlook the Madrasa Tsanawiyah (MTs) level and lack a comprehensive management perspective. This study aims to analyze the management strategy of Islamic education at MTs Negeri 1 Pandeglang, explore the central role of leadership, and formulate a conceptual model for sustainable quality improvement. Using a qualitative case study design, data were collected over six months through in-depth interviews, participatory observations, documentation, and Focus Group Discussion (FGD). Data analysis followed the interactive model of Miles, Huberman, and Saldaña. The findings reveal three integrated strategic pillars supporting madrasa success. First, collaborative-participatory management revitalizes the principle of shura, fostering collective ownership among stakeholders. Second, visionary-religious leadership combines transformational leadership with spiritual role modeling (uswatun hasanah). Third, the systematic internalization of Islamic values builds a holistic quality culture by integrating Total Quality Management (TQM) with character development (akhlakul karimah). This study offers an empirically grounded and contextually relevant conceptual model that can serve as a practical reference for policymakers and practitioners to enhance the sustainable quality of madrasa education.